Experiences of childbirth in Natal Indian women - H.B. Brookes (AOSIS, 1991)
Through fifteen in-depth case studies of primipara, Natal Indian women's experiences of childbirth have been described Common problems were identified, including lack of a family support person throughout labour, lithotomy position for delivery, episiotomies and their sequelae, breast-feeding difficulties and lack of professional support in the early puerperium at home. Preparation for common medical interventions in labour, breast-feeding and parenting appeared inadequate. Pertinent sociocultural aspects have been identified. These include continuing family support and culturally prescribed behaviour pertaining most importantly to the early puerperium and affecting the maternal-neonatal dyad. In the early adaptation to motherhood informants continued their role as daughter or daughter-in-law and would only actively continue their role as wife later or at the end of the puerperium. These traditional patterns of behaviour persist despite marked changes in educational level, language spoken and employment status. In the light of this research and founded on scientific evidence, a number of recommendations are made and areas for further research are identified